2014
DOI: 10.1007/s00259-014-2691-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 18F-DOPA PET/CT at the time of recurrence in patients affected by neuroblastoma

Abstract: Our results confirm the good agreement between (18)F-DOPA PET/CT and (123)I-MIBG scan in patients affected by NB relapse. In time-to-event analyses, (123)I-MIBG scan and (18)F-DOPA PET/CT scores were independently and significantly associated with disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 25 publications
3
64
0
1
Order By: Relevance
“…In a small study, sensitivity and specificity of approximately 90% were reported in stage III/IV neuroblastoma patients (67), with visualization of more disease sites and better assessment of response than with 123 I-MIBG (68). 18 F-DOPA lesion scores have also been evaluated, and a preliminary assessment showed a high correlation with the MIBG score (69). A higher prognostic correlation of metabolic burden detected with 18 F-DOPA was noted in this study.…”
Section: Other Net-targeting Tracerssupporting
confidence: 50%
“…In a small study, sensitivity and specificity of approximately 90% were reported in stage III/IV neuroblastoma patients (67), with visualization of more disease sites and better assessment of response than with 123 I-MIBG (68). 18 F-DOPA lesion scores have also been evaluated, and a preliminary assessment showed a high correlation with the MIBG score (69). A higher prognostic correlation of metabolic burden detected with 18 F-DOPA was noted in this study.…”
Section: Other Net-targeting Tracerssupporting
confidence: 50%
“…In addition, patients with a 18 F-DOPA WBMB [7.5 displayed a significantly higher risk of disease progression and death than those with 18 F-DOPAWBMB B7.5 [34]. At multivariate analysis, including all principals prognostic factors at the time of NB relapse, the authors report a significant association between 123 I-mIBG score and 18 F-DOPA WBMB with respect to progression free survival (PFS).…”
Section: Comparison With Conventional Radiological Imagingmentioning
confidence: 96%
“…In this context, only the paper by Piccardo and colleagues evaluated the prognostic role of 123 I-mIBG scintigraphy and 18 F-DOPA-PET/CT at the time of NB relapse [34]. Firstly, the authors introduced a new 18 F-DOPA-PET/CT score to assess the whole-body burden of NB.…”
Section: Comparison With Conventional Radiological Imagingmentioning
confidence: 99%
“…FDG PET has been shown to be of prognostic value [18]. 68 Ga-DOTATATE PET [19,20], 18 F-fluorodopa PET [21,22] and labeled monoclonal antibody scans [23] may also be of value. Nonetheless, despite this embarrassment of riches in the techniques available for imaging neuroblastoma, 123 I-mIBG remains the gold standard, and semi-quantitative skeletal scoring as described by Lewington et al [1] should become the new norm.…”
mentioning
confidence: 99%